Acupuncture for drooling in children with cerebral palsy: A protocol for systematic review. Issue 14 (9th April 2021) - Xiong, Wei; Cheng, Ling; Tang, Genhua; Hou, Xinju; Zhu, Manhua; Lu, Lunbin; Zhong, Zhiying
Abstract: Background: The aim of this study is to provide the methods used to evaluate the effectiveness and safety of acupuncture therapy for treating drooling in children with cerebral palsy. Methods and analysis: A comprehensive search of Pubmed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, 4 Chinese databases (China National Knowledge Infrastructure, Chinese Biomedical Literatures database, Wan-Fang Database and Chinese Science and Technology Periodicals will be conducted to identify randomized controlled trials of acupuncture for treating children with cerebral palsy salivation with no restriction on time or language. The primary outcome of this systematic review will be the effective rate. The risk of bias will be implemented according to Cochrane Handbook for Systematic Reviews of Interventions. We will conduct the meta-analysis to synthesize the evidence for each outcome, if possible. The heterogeneity will be evaluated statistically using the χ 2 test and the I 2 statistic. The random-effect model will be used to provide more conservative results, if significant heterogeneity is identified ( I 2 > 50% or P < .10). Ethics/dissemination: Our findings will be disseminated in a peer-reviewed journal and at conference meetings. It is not necessary for formal ethical approval as no primary data are collected. Trial registration number: INPLASY2020110024